1972
DOI: 10.2134/jeq1972.00472425000100010015x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Thermal Aspects of Pesticide Disposal

Abstract: Pesticides, when treated with sodium biphenyl reagent, were decomposed to the extent of 80 to 99%. However, when these compounds were treated with a mixture of metallic sodium and liquid ammonia, 15 of the 19 compounds were completely degraded. When metallic lithium was substituted for metallic sodium, the mixture was less effective but still completely degraded 8 of 19 compounds. The decomposition products resulting from these reactions were not tested for toxicity.The pesticide formulations were incinerated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Also, some of the emulsifiers used in herbicide formulations are ineffective or become inactivated in concentrated salt solutions such as liquid fertilizer solutions. 3 Fertilizer salts have been recommended as contact herbicides and the addition of proper wetting agents can nearly double their contact effectiveness (4). Mitchell et al (6) found that atrazine [2-chloro-4-(ethylamino)-6• (isopropylamino)-s-triazine]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some of the emulsifiers used in herbicide formulations are ineffective or become inactivated in concentrated salt solutions such as liquid fertilizer solutions. 3 Fertilizer salts have been recommended as contact herbicides and the addition of proper wetting agents can nearly double their contact effectiveness (4). Mitchell et al (6) found that atrazine [2-chloro-4-(ethylamino)-6• (isopropylamino)-s-triazine]…”
mentioning
confidence: 99%
“…No herbicide degradation occurred where trifluntlin, butylate, or alachlor were combined with 3-10-10, 28-0-0, or 4-12-24 liquid fertilizers (1). Kennedy et al (3) found that liquid ammonia combined with metallic sodium or lithium would degrade atrazine, trifluralin, and 2,4-D [ (2,4-dichlorophenoxy)acetic acid].…”
mentioning
confidence: 99%
“…Also, from the branches (trichlorophenol, C-C, C-O and C-H bonds), decomposition of chlorophenols moiety will form gases such as CO, CO 2 , Fig. 2 Zero-point charge (pH zcp ) of EET polymer Cl 2 , and HCl [29]. It can be concluded from these results that the compound is thermally stable.…”
Section: Thermogravimetric Analysis and Differential Scanning Calorimetrymentioning
confidence: 90%
“…Several review articles have appeared that address the broad application of the chemistry (Watt, 1950;Birch, 1950;Birch, 1958). Organic phosphorous and sulfur compounds such as pesticides and chemical warfare agents are known to be reactive to solvated electrons (Kennedy et al, 1972). It is also well understood that aromatic materials such as benzene and polyaromatic hydrocarbons are chemically reduced by the Birch reaction using solvated electrons (Birch, 1950).…”
Section: Background On the Chemistrymentioning
confidence: 99%